Microplastic Distribution in Beach Sediments: Comparison Between the North and South Waters of East Java Island, Indonesia - Defri Yona; Fahreza Okta Setyawan; Sisylia Eka Narriyah Putri; Feni Iranawati; Muhammad Ariq Kautsar; Atsuhiko Isobe (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research This is the first study of microplastics in four beach sediments in the east part of Java Island. Bahak and Pesona Beach are connected to Java Sea (north part), while Tambak Rejo and Balekambang Beach are connected to Indian Ocean (south part). A higher microplastics were observed on the beaches of the north part compared to the south part. Local sources and oceanographic parameters of the beaches influence the presence of microplastics in the study areas. Abstract Microplastic pollution in beach sediments has been studied intensively worldwide, but there are limited studies in the beach areas of the eastern Java Island, Indonesia. This study aimed to identify the distribution of microplastic in four beaches in Indonesia: Bahak, Pesona, Tambakrejo, and Balekambang. The first two beaches are located in the north of Java Island and influenced by the east Java Sea, while the last two are located in the south and influenced by the Indian Ocean. Sediment samples were collected along the strandline inside the 1 í— 1 m transect quadrate in the top 5 cm using a stainless-steel shovel. Microplastic and granulometry analyses were conducted to obtain microplastic and sediment grain size data, respectively. Physical parameters of the beaches, such as wind, wave, and ocean current, were calculated using Copernicus and NASA (PODAAC), respectively. The total abundance of microplastic ranged from 54.7 ± 48.6 to 103.3 ± 4.7 particles kg-1 with the following descending order: Bahak > Pesona > Tambakrejo > Balekambang. Although there was no statistically significant difference in microplastic concentrations among the beaches, the beaches connected to the Java Sea accumulated more microplastics than the ones connected to the Indian Ocean. Fiber and blue were the dominating type and colors of microplastic. The results confirm that the distribution of microplastic is associated with the morphology of the beaches and the local source.